2017
DOI: 10.5603/gp.a2017.0066
|View full text |Cite
|
Sign up to set email alerts
|

See and treat strategy by LEEP conization in patients with abnormal cervical cytology

Abstract: Results: Overtreatment rate was found to be 46.6%, decreasing with higher grade of cervical smear abnormalities. Age more than 45, low grade of cervical cytologic abnormality and absence of glandular involvement were associated with higher overtreatment rates. The more advanced the histopathology, the more increased risk of surgical margin on LEEP and ECC positivity (p < 0.0001, for both). Glandular involvement was associated with both surgical margin and ECC positivity.Conclusions: S & T can be used in patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…Under clinical conditions including: an unsatisfactory colposcopy; atypical squamous cells of undetermined significance (ASCUS) in cytology and positive HPV but without visible lesion under the colposcopy; ≥LSIL in cytology and no lesion under colposcopy; HSIL cytology; atypical glandular cells (AGC); or a suspected invasive disease, ECC was suggested as the prioritizable method ( 30 ). In our study, we also found that the HSIL of ECC was a risk factor for positive margins, which was supported by the previous study that the risk of surgical margins with positive ECC was increased ( 31 ). At present, TCT and ECC are mainly used for cervical cancer screening and diagnosis, but their impact on prognosis is often ignored clinically.…”
Section: Discussionsupporting
confidence: 91%
“…Under clinical conditions including: an unsatisfactory colposcopy; atypical squamous cells of undetermined significance (ASCUS) in cytology and positive HPV but without visible lesion under the colposcopy; ≥LSIL in cytology and no lesion under colposcopy; HSIL cytology; atypical glandular cells (AGC); or a suspected invasive disease, ECC was suggested as the prioritizable method ( 30 ). In our study, we also found that the HSIL of ECC was a risk factor for positive margins, which was supported by the previous study that the risk of surgical margins with positive ECC was increased ( 31 ). At present, TCT and ECC are mainly used for cervical cancer screening and diagnosis, but their impact on prognosis is often ignored clinically.…”
Section: Discussionsupporting
confidence: 91%
“…The final outcome, separated into 2 predefined situations A and B, showed the following results: in 7 articles with situation A (negative colposcopy not followed by a biopsy), [11, 14, 15, 21, 23, 24, 34] the mean PPV of HSIL for histological CIN2+ was 66.3%. In situation B (negative colposcopy followed by a four-quadrant punch biopsy or random biopsies), 15 included studies [5, 9, 12, 15, 16, 18, 20, 22, 25, 26, 28-31, 33] showed a mean PPV of 78.6%.…”
Section: Resultsmentioning
confidence: 99%
“…The remaining 15 articles did not clearly describe the method of cytology [5, 9-11, 14, 17, 19, 20, 28-34]. Concerning the version of the Bethesda classification, the most frequently reported version was the 2001 classification, with the exception of 3 articles [11, 15, 21] in which the 1991 version was applied.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation